Anti-angiogenic effects of the tubulysin precursor pretubulysin and of simplified pretubulysin derivatives - Rath, S (Blackwell Publishing Ltd, 2012)
BACKGROUND AND PURPOSE: The use of tubulin-binding compounds, which act in part by inhibiting tumour angiogenesis, has become an integral strategy of tumour therapy. Recently, tubulysins were identified as a novel class of natural compounds of myxobacterial origin, which inhibit tubulin polymerization. As these compounds are structurally highly complex, the search for simplified precursors [e.g. pretubulysin (Prt)] and their derivatives is mandatory to overcome supply problems hampering clinical development. We tested the anti-angiogenic efficacy of Prt and seven of its derivatives in comparison to tubulysin A (TubA). EXPERIMENTAL APPROACH: The compounds were tested in cellular angiogenesis assays (proliferation, cytotoxicity, cell cycle, migration, chemotaxis, tube formation) and in vitro (tubulin polymerization). The efficacy of Prt was also tested in vivo in a murine subcutaneous tumour model induced with HUH7 cells; tumour size and vascularization were measured. KEY RESULTS: The anti-angiogenic potency of all the compounds tested ran parallel to their inhibition of tubulin polymerization in vitro. Prt showed nearly the same efficacy as TubA (EC(50) in low nanomolar range in all cellular assays). Some modifications in the Prt molecule caused only a moderate drop in potency, while others resulted in a dramatic loss of action, providing initial insight into structure–activity relations. In vivo, Prt completely prevented tumour growth and reduced vascular density to 30%. CONCLUSIONS AND IMPLICATIONS: Prt, a chemically accessible precursor of some tubulysins is a highly attractive anti-angiogenic compound both in vitro and in vivo. Even more simplified derivatives of this compound still retain high anti-angiogenic efficacy.